Photo‐Crosslinkable Unnatural Amino Acids Enable Facile Synthesis of Thermoresponsive Nano‐ to Microgels of Intrinsically Disordered Polypeptides. Issue 5 (11th December 2017) - Costa, Simone A.; Simon, Joseph R.; Amiram, Miriam; Tang, Lei; Zauscher, Stefan; Brustad, Eric M.; Isaacs, Farren J.; Chilkoti, Ashutosh
Abstract: Hydrogel particles are versatile materials that provide exquisite, tunable control over the sequestration and delivery of materials in pharmaceutics, tissue engineering, and photonics. The favorable properties of hydrogel particles depend largely on their size, and particles ranging from nanometers to micrometers are used in different applications. Previous studies have only successfully fabricated these particles in one specific size regime and required a variety of materials and fabrication methods. A simple yet powerful system is developed to easily tune the size of polypeptide‐based, thermoresponsive hydrogel particles, from the nano‐ to microscale, using a single starting material. Particle size is controlled by the self‐assembly and unique phase transition behavior of elastin‐like polypeptides in bulk and within microfluidic‐generated droplets. These particles are then stabilized through ultraviolet irradiation of a photo‐crosslinkable unnatural amino acid (UAA) cotranslationally incorporated into the parent polypeptide. The thermoresponsive property of these particles provides an active mechanism for actuation and a dynamic responsive to the environment. This work represents a fundamental advance in the generation of crosslinked biomaterials, especially in the form of soft matter colloids, and is one of the first demonstrations of successful use of UAAs in generating a novel material. Abstract : Thermoresponsive hydrogel particles that span four orders of magnitude in size, from the nano‐ to microscale, are developed using photo‐crosslinkable unnatural amino acids. These particles are fabricated from a single starting material, an intrinsically disordered polypeptide, using self‐assembly and microfluidic templating. The particles are highly stable following crosslinking with ultraviolet light and exhibit a tunable, dynamic response to temperature.